Association between the speaking space of /s/ sound and incisal overlaps in dentate and edentate subjects - Souza, Raphael Freitas De [UNESP]; Compagnoni, Marco Antonio [UNESP]; Leles, Cláudio Rodrigues; Sadalla, Karina Buainain De Freitas [UNESP] (Faculdade De Odontologia De Bauru - USP, 2005)
The purpose of this study is to determine the association of speaking space of /s/ sound with vertical and horizontal overlaps for two subject groups. Group I comprised 61 subjects with complete permanent dentition and Group II comprised 33 complete denture wearers. They had their mandibular movement determined by using an electromagnetic method. Speaking space of /s/ was obtained from each subject as they were instructed to say the word 'seis' three times. The mean interocclusal distance during /s/ production was considered the speaking space of /s/. Vertical and horizontal incisor overlaps were also measured. The mean value of speaking space of /s/ was 2.22 mm (± 1.38) for Group I and 2.61 mm (± 1.53) for Group II. In Group I, significant correlations were found between the speaking space of /s/ and vertical overlap (r=0.36, P<0.01), and between speaking space of /s/ and horizontal overlap (r=0.45, P<0.01). In Group II, no significant correlation was found between speaking space of /s/ and the overlaps. It was concluded that incisor overlap had a direct influence on the measure of speaking space of /s/ for dentate subjects, but this association was not present for complete denture wearers.

O objetivo deste estudo foi determinar a associação do espaço de pronúncia do som /s/ com os trespasses vertical e horizontal em dois grupos de indivíduos. O Grupo I foi formado por 61 indivíduos com dentição permanente completa e o Grupo II por 33 usuários de próteses totais. Todos tiveram seus movimentos mandibulares determinados por um método eletromagnético. O espaço de pronúncia do /s/ foi obtido em cada indivíduo conforme eram instruídos a dizer a palavra 'seis' por três vezes. A distância interoclusal média durante a produção do /s/ foi considerada como sendo o espaço de pronúncia do /s/. Os trespasses incisais vertical e horizontal também foram mensurados. Os valores médios do espaço de pronúncia do /s/ foram 2.22 mm (± 1.38) para o Grupo I e 2.61 mm (± 1.53) para o Grupo II. Para o Grupo I, observou-se associação entre o espaço de pronúncia do /s/ e os trespasses vertical (r=0.36, P<0.01) e horizontal (r=0.45, P<0.01). Para o Grupo II, não foi encontrada nenhuma correlação significante entre o espaço de pronúncia do /s/ e os trespasses. Concluiu-se que o trespasse incisal teve influência direta sobre as medidas do espaço de pronúncia do /s/ em indivíduos dentados, mas esta associação não esteve presente nos usuários de próteses totais.
Associação entre o espaço de pronúncia do som /s/ e os trespasses incisais em indivíduos dentados e edentados
Keywords: Phonetics; Dental occlusion; Complete denture; Jaw relation record; Fonética; Oclusão dentária; Prótese total; Registro da relação maxilomandibular